In Vitro Comparison of Two Different Mechanical Circulatory Support Devices Installed in Series and in Parallel. Issue 9 (9th April 2014) - Rezaienia, Mohammad Amin; Rahideh, Akbar; Rothman, Martin Terry; Sell, Scott A.; Mitchell, Kyle; Korakianitis, Theodosios
Abstract This study investigates the novel approach of placing a ventricular assist pump in the descending aorta in series configuration with the heart and compares it with the two traditional approaches of left‐ventricle‐to‐ascending‐aorta (LV‐AA) and left‐ventricle‐to‐descending‐aorta (LV‐DA) placement in parallel with the heart. Experiments were conducted by using the in‐house simulator of the cardiovascular blood‐flow loop (SCVL). The results indicate that the use of the LV‐AA in‐parallel configuration leads to a significant improvement in the systemic and pulmonic flow as the level of continuous flow is increased; however, this approach is considered highly invasive. The use of the LV‐DA in‐parallel configuration leads to an improvement in the systemic and pulmonic flow at lower levels of continuous flow but at higher levels of pump support leads to retrograde flow. In both in‐parallel configurations, increasing the level of pump continuous flow leads to a decrease in pulsatility to a certain extent. The results of placing the pump in the descending aorta in series configuration show that the pressure drop upstream of the pump facilitates cardiac output as a result of afterload reduction. In addition, the pressure rise downstream of the pump may assist with renal perfusion. However, at the same time, the pressure drop generated at the proximal part of the descending aorta induces a slight drop in carotid perfusion, which would be autoregulated by the brain in a native cardiovascular system. The pulse wave analysis shows that placing the pump in the descending aorta leads to improved pulsatility in comparison with the traditional in‐parallel configurations.